RATIONAL MODES OF GAS TRANSPORT SYSTEMS IN THE CONDITIONS OF UNSTATIONARY GAS TRANSPORT - Grudz, V. Ya.; Grudz, Y. V.; Stasyuk, R. B.; Bavolyak, V. I.; Kapushchak, Y. S.; Turovskyi , O. A. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2023)
The problem of rational regulation of the operation modes of the gas transportation system, which is operated in conditions of non-stationary gas transportation, is considered. An assessment of the mathematical modeling of non-stationary processes in complex gas transport systems with uneven gas consumption and diversification of sources of energy supply is given. Based on analytical studies, recommendations are made on the influence of various parameters on the efficiency of compressor station operation. Dependencies are obtained that express the nature of gas transport process control, which can be applied in each specific case to determine the response of the system to a change in the control factor. Modeling of non-stationary objects of gas transport systems should be carried out using an adaptive linearized system, which implements the principle of energy-efficient regulation, i.e. it allows to specify the parameters of the technological object and control its operation at the same time. As the analysis showed, the given technological constraints on pressure are presented in terms of changes in productivity and can be combined with constraints on the productivity of the compressor station. The obtained limits of technological admissibility for the average daily gas consumption are not constants, but some functions of time, the behavior of which is determined by the nature of gas consumption. The use of the specifics of the interrelationship of restrictions caused by the technology of gas transport, in order to build simpler algorithms for its solution, made it possible to create a methodology for forecasting the system’s operating modes in conditions of non-stationary gas consumption.